Local Application of Timolol 0.5% Solution in Treating Chronic Non-Healing Ulcers – A Prospective Study - Valluru, Sivaramakrishna; R, Ramachandra; Chandana, Jyothi Sasikanth (Journal of Fundamental and Applied Pharmaceutical Science, 2023)
Chronic non-healing ulcers are a variety of ulcers that occur mainly over the lower limb and are resistant to conventional therapy. There are modern treatments like various types of dressings and topical preparations available in the market. However, they are costly and may not be freely available to the general population. Topical usage of  β2-AR  antagonists like timolol may promote wound healing by enabling keratinocyte migration into the wound to initiate the re-epithelisation. The objective of this study is to assess the effectiveness of topical timolol 0.5% in accelerating the wound healing process by observing the signs of healing. It is a prospective observational study conducted in Government General Hospital, Rangaya Medical Medical College, Kakinada, after getting  Institutional Ethical Committee approval from March 2021 to March 2023. One hundred patients with Chronic non-healing foot ulcers were taken for this study. Mean age was 47.64.60% of the study population was in the 20-55 years age group. Reduction in mean ulcer area was on day 15 and day 30 with topical application of timolol.